2006
DOI: 10.1002/chem.200501042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Folding Behavior of β‐Amino Acid Derived Polyisocyanides

Abstract: Helical polymers of isocyanopeptides derived from beta-amino acids have been synthesized and their architectures have been studied in detail. Similar to their alpha-amino acid analogues, the helical conformation in these macromolecules is stabilized by internal hydrogen-bonding arrays along the polymeric backbone. Unexpectedly, the flexibility of the beta-peptide side arms results in a rearrangement of the initial macromolecular architecture, leading to a more stable helical structure possessing a better defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Similar hydrogen‐bonding‐assisted helix formation and stabilization was reported by Nolte and co‐workers for poly(isocyanopeptide)s, although the helices unfold irreversibly at high temperature 3d. 9a,b, 15…”
Section: Resultssupporting
confidence: 75%
“…Similar hydrogen‐bonding‐assisted helix formation and stabilization was reported by Nolte and co‐workers for poly(isocyanopeptide)s, although the helices unfold irreversibly at high temperature 3d. 9a,b, 15…”
Section: Resultssupporting
confidence: 75%
“…43 Polyisocyanides derived from b-amino acids were also reported to revert, on standing in solution, from a kinetically determined structure to a thermodynamically more stable one, as reflected in the CD spectra. 44 Interestingly, for these polymers it was observed that both the helical arrangement and the hydrogen-bonding network remained intact and only minor changes occurred in the corresponding spectra. For PIAG during polymerization, a transition was already observed to a state with only little secondary structure.…”
Section: Synthesis Of Block Copolymersmentioning
confidence: 94%
“…Helical poly(isocyanopeptide)s 15 and 16 derived from b-amino acids were synthesized ( Figure 8.3) [22]. Like their a-amino acid analogs, the helical conformation in these polymers is stabilized by internal hydrogen-bonding arrays.…”
Section: Synthesis Of Poly(isocyanide)s Bearing Amino Acid Andmentioning
confidence: 99%